Out of Africa: biogeographic history of the open‐habitat chats (Aves, Muscicapidae: Saxicolinae) across arid areas of the old world. (1st January 2016) - Alaei Kakhki, Niloofar; Aliabadian, Mansour; Schweizer, Manuel
Abstract : Arid and semi‐arid areas constitute a prominent feature of the earth today, especially in Asia and Africa. Their formation started in the middle Miocene with increased stepwise aridification since the Pliocene. This aridification had strong ecological and evolutionary consequences and not only led to fragmentation of moist‐adapted biota, but also fostered the evolution of arid‐adapted taxa from mesic ancestors and triggered speciation within arid areas. The open‐habitat chats, a clade within Saxicolinae (Aves, Muscicapidae), constitute one of the most significant arid‐adapted passerine groups of Africa and Eurasia. Here, we present a temporal and spatial framework for the diversification of open‐habitat chats, using probabilistic approaches for the reconstruction of their biogeographic history based on a time‐calibrated multilocus molecular phylogenetic hypothesis. The diversification of open‐habitat chats was initiated in the late Miocene at around 7.4 Ma, most likely in sub‐Saharan Africa. Southern Africa and the Horn of Africa acted as centres of diversification and biogeographic expansion. From the latter area, the Arabo‐Sindic region and subsequently further parts of Eurasia and North Africa were colonized. The colonization history out of sub‐Saharan Africa contrasts with that of several other songbird clades, where a biogeographic expansion from Eurasia or northern Africa to southern Africa was prevalent. Habitat fragmentation through forest expansions during intermittent wetter periods in Africa influenced diversification in several clades. However, phases of increased aridity, with hyperarid regions acting as drivers of vicariance, seem to have also been important in radiations of the Arabo‐Sindic region and the Horn of Africa during the Pleistocene. Different processes such as colonization of new areas followed by vicariance or speciation across ecotones might have played a role throughout the radiation of open‐habitat chats.